Effectiveness of Nursing Counseling on Reliefs Psychological Burdens upon women after Mastectomy - Iqbal M. Abbas; Rusul S. Ghazal (Kufa Journal for Nursing Sciences)
Objective: To identify the effectiveness of nursing counseling on psychological burdens on women after mastectomy.